1999
DOI: 10.1021/jp984759x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Neutral and Ion-Pair Clusters of Hydrated Sulfuric Acid H2SO4(H2O)n (n = 1−5)A Molecular Orbital Study

Abstract: Various isomeric structures of the hydrated clusters of sulfuric acid, H2SO4(H2O) n (n = 1−5), are examined using a density functional molecular orbital method. Due to the small energy difference between trans and cis conformations about two OH groups of sulfuric acid, there are three types of isomeric forms of the hydrated clusters of sulfuric acid which involve the proton nontransferred trans conformer, the proton transferred trans conformer, and the proton nontransferred cis conformer of sulfuric acid. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
216
9
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(259 citation statements)
references
References 43 publications
(83 reference statements)
33
216
9
1
Order By: Relevance
“…d Calculated using the 6-31G** basis set, and at 230 K. e Bandy and Ianni. 4 f Re et al 5 Note that their reported value of ∆S corresponded to -1 times the ∆S value given here, as they used a different sign convention. g Ding et al 6 h Al Natsheh et al 7 Note that the temperature used was 298.…”
Section: Computational Detailsmentioning
confidence: 73%
See 2 more Smart Citations
“…d Calculated using the 6-31G** basis set, and at 230 K. e Bandy and Ianni. 4 f Re et al 5 Note that their reported value of ∆S corresponded to -1 times the ∆S value given here, as they used a different sign convention. g Ding et al 6 h Al Natsheh et al 7 Note that the temperature used was 298.…”
Section: Computational Detailsmentioning
confidence: 73%
“…1,2 To obtain structural and thermochemical parameters for, e.g., nucleation simulations, ab initio and density functional theory calculations have been carried out on sulfuric acid hydrates [3][4][5][6][7] and sulfuric acid-ammonia-water clusters. 8,9 However, the results obtained in different studies vary strongly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the M06-2X functional because of its performance for related systems (Walker et al, 2013;Lengyel et al, 2017b). Localized structures, including hydrogen-bonded (H 2 SO 4 · · · H 2 O) and ion-pair (HSO − 4 · · · H 3 O + ) structures, are in excellent agreement with the literature (Re et al, 1999;Henschel et al, 2014). All calculations were performed with the Gaussian 09 software package (Frisch et al, 2013) and ABIN code was used for molecular dynamics (Hollas et al, 2015).…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…Progressive hydration of sulfuric acid increases the probability for proton transfer from the acid to water. Theoretical calculations predict the covalently bonded H 2 SO 4 as the global minima for H 2 SO 4 (H 2 O) n clusters with n ≤ 4, while for n = 3 and 4 the hydrogen-bonded (H 2 SO 4 ··· H 2 O) and ion-pair (HSO − 4 ·· · H 3 O + ) structures are energetically very close and both structures coexist for these clusters (Re et al, 1999;Temelso et al, 2012a). Upon further hydration H 2 SO 4 (H 2 O) n for n ≥ 5 the ion-pair structures become the global energy minima.…”
Section: Introductionmentioning
confidence: 99%